THE EFFECTIVENESS OF ORAL TESTS AS AN ASSESSMENT TOOL FOR ARABIC AT THE NURUL HUDA ISLAMIC BOARDING SCHOOL IN SUKAWINATAN - Muhammad Rijaldi; Jumhur Jumhur; Qoim Nurani (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study investigates the effectiveness of oral tests as an assessment instrument for Arabic speaking skills at Pondok Pesantren Nurul Huda Sukawinatan. Using a mixed-methods approach with a sequential explanatory design, the research combines a quasi-experimental pretest-posttest control group design with qualitative data from interviews and observations. Quantitative analysis, specifically the independent sample t-test, showed a significant improvement in the speaking skills of the experimental group (p < 0.05), demonstrating the positive impact of oral testing. The average score of the experimental group increased from 61.4 in the pretest to 82.7 in the posttest, reflecting substantial progress after the treatment. This finding is supported by qualitative data, which revealed that oral tests provide a more authentic evaluation, boost student motivation, and encourage practical speaking practice. The study concludes that oral tests are highly effective for assessing Arabic speaking skills in this context, offering a valuable contribution to authentic assessment literature and providing practical recommendations for educators, language teachers, curriculum designers, and future researchers.